Strategi Digital Learning dalam Meningkatkan Efisiensi Proses dan Hasil Pembelajaran - Arina Asmal Hidayah; Junadhan Syapa Widyaksa; Arip Rizky; Syarifuddin Syarifuddin; Rani Oktapiani (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This study is motivated by the development of digital technology, which has driven a transformation in the learning paradigm from conventional models to more flexible, interactive, and innovative technology-based learning. Changes in student characteristics in the digital era require adaptive learning strategies that are able to improve both the efficiency of the learning process and learning outcomes. This study aims to describe and analyze digital learning strategies in enhancing learning efficiency and their impact on student achievement. The research employs a qualitative approach using a literature review by examining various relevant scientific sources related to the concepts, characteristics, implementation, and impacts of digital learning. The data were analyzed using content analysis techniques to produce a systematic conceptual framework. The findings indicate that systematically designed digital learning strategies can improve conceptual understanding through interactive content delivery, strengthen students’ motivation and independent learning, and enhance retention and learning mastery. Learning efficiency is reflected in flexible access, time optimization, and technology-based assessment. However, its implementation still faces challenges such as limited infrastructure and digital literacy. Therefore, careful planning and the improvement of digital competencies are necessary to ensure that digital learning can be implemented effectively and sustainably in improving the quality of education.